Fully spectrum-sliced four-wave mixing wavelength conversion in a semiconductor optical amplifier - Ian Forsyth, David; Tariq, Kanar Roshen; Abdullah Al-Gburi, Ahmed Jamal (Wydawnictwo SIGMA-NOT, 2024)
The semiconductor optical amplifier device has garnered significant interest in recent years, both in academic and commercial circles. This diminutive yet remarkable device has been the focus of numerous academic papers, primarily due to its multifunctionality and gain capabilities. In this study, four-wave mixing (FWM) wavelength conversion was successfully achieved in an SOA using a single, cost-effective spectrum-sliced incoherent source for both pump and probe. This concept holds substantial potential for application in future cost-effective, fully spectrum-sliced systems.